A Program of Professional Postgraduate Education in Transfusion Medicine for the Specialty of Anesthesiology and Reanimation - Torres Romo, Ubaldo Roberto; Fernández Franch, Neyda; Menéndez Cabezas, Arturo Teodoro; López Lazo, Sarah Estrella (Revista Cubana de Investigaciones Biomédicas, 2020)
Introduction: The higher medical education identifies different learning needs to develop professional postgraduate courses. Objective: The research objective was to propose a program of professional postgraduate education for the development of the competency in transfusion medicine for the specialty Anesthesiology and Reanimation in Camagüey. Materials and Methods: An educational study at the Camagüey University of Medical Sciences from March 2016 to December 2017 was carried out, in which both quantitative and qualitative methods were employed. The elements of the competency in transfusion medicine within the context of Anesthesiology and Reanimation specialty in Cuba were outlined. Results: A program of a diploma course was designed, based on curricular development of medical education and the identified learning needs. It was characterized by flexibility, systematic teaching and a learner’s centered approach. More than half the specialists who validated the proposal through the variables that characterize the program coincided, according to the non-parametric Kendal test, in giving out an evaluation of excellent. Specialists and residents of Anesthesiology and Reanimation, as well as technicians of transfusion medicine participated in the first version of the diploma course, considered as a pre experiment, which was taught by professors with experience in transfusion, experts of blood banking, as well as basic biomedical and clinical sciences professors. A progressive, systematic and comprehensive approach to the optimal use of blood components was encouraged. Conclusions: Learners unanimously evaluated the diploma course as positive in order to enhance professional skills, and to update their knowledge of transfusion medicine, also considered as very good the teachers’ preparation and the availability of up-to-date literature. Technicians expressed their satisfaction for the opportunity of scientific exchange with professionals of anesthesiology and reanimation.